Global and regional burdens of opioid use disorder from 1990 to 2021, with future forecasts to 2050: a systematic analysis for the global burden of disease study 2021 - Cao, Juanzhao; Li, Ruxin; Hu, Guangjun; Huang, Wanqiang (Frontiers in Public Health, 2025)
IntroductionThis study comprehensively investigated the magnitude and temporal trends of the global burden of opioid use disorder (OUD) from 1990 to 2021 and predicted the disease burden in the next 29 years.MethodsThe data originated from the Global Burden of Disease 2021 study. Incidence, prevalence, deaths, and disability-adjusted life years (DALYs) were analyzed by age-standardized rates. The estimated annual percentage change was calculated. The decomposition analysis was used to analyze the changes in burden globally and across the five social demographic index (SDI) regions from 1990 to 2021, with the affected population broken down into three key determinants at the group level: population aging, population growth, and epidemiological changes. Age-period-cohort analysis was used to estimate age, period, and cohort effects. Bayesian age-period-cohort modeling was used to predict the burden of OUD from 2021 to 2050.ResultsIn 2021, the global age-standardized prevalence rate (ASPR), age-standardized incidence rate (ASIR), age-standardized deaths rate (ASDR), and age-standardized DALYs rate of OUD were 198.489 [95% Uncertainty Interval (95%UI): 173.423-227.218], 24.544 (95%UI: 20.739-29.476), 1.194 (95%UI: 1.115-1.294), and 137.146 (95%UI: 112.293 -161.385) per 100,000 people, respectively. Among the 21 GBD regions, in 2021, High-income North America had the highest ASPR, ASIR, ASDR, and age-standardized DALYs rate of OUD. Overall, the global burden of OUD among males was significantly higher than that among females, especially in terms of deaths and DALYs. In terms of prevalent cases, globally, aging contributed 1.29%, population growth contributed 61.74%, and epidemiological changes contributed 36.97% to the increase in the burden of OUD. The global prevalence rate increased with age among people aged 20-30, decreased with age among those aged 30-80, and increased with age among people over 80. For males, the predicted ASPR, ASIR, ASDR, and age-standardized DALYs rate for OUD in 2050 are 239.62, 31.98, 2.42, and 206.44 per 100,000 people, respectively.DiscussionThis study highlighted the substantial burden of OUD, particularly in High-income North America, young populations, and male populations. Population growth and epidemiological changes contributed significantly to the increase in the burden of OUD.